2017
DOI: 10.3399/bjgp17x691865
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term benzodiazepine and Z-drugs use in England: a survey of general practice

Abstract: More than a quarter of a million people in the UK are likely to be taking highly dependency-forming hypnotic medication far beyond the recommended time scales. As there is evidence that long-term use of BZDs causes adverse physiological and neurological effects, and protracted withdrawal (with associated complications), this represents a serious public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 7 publications
2
51
0
5
Order By: Relevance
“…Long‐term prescribing remains common with almost one‐third of individuals receiving prescriptions for more than 3 months. This is comparable to recent data from the UK and US . In addition, the most common quantities dispensed were for 4‐week periods, despite guidelines recommending that individuals receiving these medications on a long‐term basis only be issued with small medication quantities at a time (≤7‐day supply) .…”
Section: Discussionsupporting
confidence: 77%
“…Long‐term prescribing remains common with almost one‐third of individuals receiving prescriptions for more than 3 months. This is comparable to recent data from the UK and US . In addition, the most common quantities dispensed were for 4‐week periods, despite guidelines recommending that individuals receiving these medications on a long‐term basis only be issued with small medication quantities at a time (≤7‐day supply) .…”
Section: Discussionsupporting
confidence: 77%
“…In those studies, the most frequent PIMs were represented by PPIs, drugs without an indication, NSAIDs, and benzodiazepines, whereas PPOs were represented by statins, antiplatelet agents, calcium, and vitamin D. [24][25][26][27] The most prevalent PIMs observed in our study are in accordance with those from other studies. [28][29][30][31][32] A study in Romania by Primejdie et al in 2016 using the STOPP/ START criteria of 2008 showed that the drug class with the highest percentage of use was NSAIDs (56.66% of outpatients and 35.63% of hospitalized patients), followed by benzodiazepines. That study did not assess PPOs.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, benzodiazepines are frequently used [7,[13][14][15][16]. The prevalence rates of benzodiazepine use in the population vary between 2 and 17% [13]: benzodiazepine use is twice as high in women than in men, is higher in older people and is mainly long-term use [13].…”
Section: Introductionmentioning
confidence: 99%